2020
DOI: 10.1159/000505664
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Germline Mutations in Chinese Patients with Gastric Cancer Identified by Next-Generation Sequencing

Abstract: Background: Gastric cancer (GC) is one of the leading causes of cancer death in China, while the nature of genetic factors related to GC has not been well-studied. Objectives: To assess the inherited genetic factors regarding pathogenic germline mutations in Chinese GC population. Methods: Genomic profiling of DNA was performed through next-generation sequencing with 381 cancer-related genes on tissue from patients with GC between January 1, 2017, and May 7, 2019. Results: 470 GC patients were included for ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The incidence of RAD50 mutations in our series is in agreement with TCGA data and previous reports. Zhou et al [ 26 ] reported 3% of RAD50 non-silent mutations in a large series of 406 Chinese samples of CRC; however, the fraction of rectal cancer was not specified and the relationship with radiotherapy treatment was not investigated [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of RAD50 mutations in our series is in agreement with TCGA data and previous reports. Zhou et al [ 26 ] reported 3% of RAD50 non-silent mutations in a large series of 406 Chinese samples of CRC; however, the fraction of rectal cancer was not specified and the relationship with radiotherapy treatment was not investigated [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In his family, nine relatives deceased for gastric cancer. Although not frequently, pathogenic variants in ATM have been previously described in patients with GC [ 80 , 81 , 82 ]. PC remains one of the most lethal solid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is the fourth and seventh leading cause of new cancer cases in males and females, respectively, and the fourth and fifth leading cause of cancerrelated death in males and females, respectively (Hyuna et al, 2021). Most new cases occur in developing countries, especially in China (Zhou et al, 2020). The global incidence of gastric cancer is 42.6% and the mortality rate is 45.0% (Ferlay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%